2015
DOI: 10.1016/j.biomaterials.2015.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Towards programming immune tolerance through geometric manipulation of phosphatidylserine

Abstract: The possibility of engineering the immune system in a targeted fashion using biomaterials such as nanoparticles has made considerable headway in recent years. However, little is known as to how modulating the spatial presentation of a ligand augments downstream immune responses. In this report we show that geometric manipulation of phosphatidylserine (PS) through fabrication on rod-shaped PLGA nanoparticles robustly dampens inflammatory responses from innate immune cells while promoting T regulatory cell abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 64 publications
0
46
0
Order By: Relevance
“…Lastly, the surface properties of particles such as charge can be modulated to mimic naturally occurring apoptotic bodies (i.e. highly negative) by coating the particle surface with synthetic (poly(ethylenealt-maleic anhydride)) or natural materials (phosphatidylserine) to mediate uptake by cell debris-clearance pathways [74, 75]. …”
Section: Apc Reprogrammingmentioning
confidence: 99%
“…Lastly, the surface properties of particles such as charge can be modulated to mimic naturally occurring apoptotic bodies (i.e. highly negative) by coating the particle surface with synthetic (poly(ethylenealt-maleic anhydride)) or natural materials (phosphatidylserine) to mediate uptake by cell debris-clearance pathways [74, 75]. …”
Section: Apc Reprogrammingmentioning
confidence: 99%
“…[84][85][86] Being able to harness apoptotic cell clearance pathways without the need to use live cells could provide great benefit toward understanding of how tolerance is generated. [80,88] For example, studies by Hess et al revealed that the dose and density at which self-antigen is delivered on QDs correlates with therapeutic efficacy. Studies using antigen coupled particles have already demonstrated efficacy in mouse models using a variety of administration strategies, including subcutaneous injection to target draining LNs, [80] oral administration to target DCs found in the gut, [85] and intravenous injection to target APCs in the liver [84] as well as the spleen.…”
Section: Delivery Of Antigen In Particulate Form Promotes Antigen-spementioning
confidence: 99%
“…Interestingly, not only the presence of PS, but also its geometrical surface disposition was found to play a role in tolerance induction. For example, Roberts et al observed that PLGA NPs displaying a nanorod-presentation were more efficient at inducing tolerogenic responses than the spherical ones [153]. …”
Section: Access Of Nanostructures To Target Cellsmentioning
confidence: 99%